2016
DOI: 10.1186/s13104-016-2171-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of DNA extraction methodology on gut microbiota research applications

Abstract: BackgroundThe effect that traditional and modern DNA extraction methods have on applications to study the role of gut microbiota in health and disease is a topic of current interest. Genomic DNA was extracted from three faecal samples and one probiotic capsule using three popular methods; chaotropic (CHAO) method, phenol/chloroform (PHEC) extraction, proprietary kit (QIAG). The performance of each of these methods on DNA yield and quality, microbiota composition using quantitative PCR, deep sequencing of the 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 19 publications
4
52
1
2
Order By: Relevance
“…Our replicate data sets were limited to only two different platforms and two hospitals, and the betweenhospital replicate data set was an unbalanced subset of the original cohort and rather small. Finally, since DNA extraction has been shown to be an important factor in microbiota composition variation (28,29), our replicate data sets did not include reisolation of the DNA, rather than reprocessing of the same DNA isolates. The DNA isolates were therefore stored until the two replicates were analyzed, which may also introduce some degree of variation.…”
Section: Figmentioning
confidence: 99%
“…Our replicate data sets were limited to only two different platforms and two hospitals, and the betweenhospital replicate data set was an unbalanced subset of the original cohort and rather small. Finally, since DNA extraction has been shown to be an important factor in microbiota composition variation (28,29), our replicate data sets did not include reisolation of the DNA, rather than reprocessing of the same DNA isolates. The DNA isolates were therefore stored until the two replicates were analyzed, which may also introduce some degree of variation.…”
Section: Figmentioning
confidence: 99%
“…However, it is difficult to mimic the complexity of real microbial communities using simplified mocks, and impossible to test for the efficiency of the extraction step for unknown/uncultured organisms. Much evidence suggests that incorporating a bead-beating step into the DNA extraction process improves yield and representativeness of resulting species profiles compared to chemical-only lysis 31,135 (ref#133 C.Q.,N.J.L.). However, this type of approach does typically result in more sheared DNA, potentially limiting the power of burgeoning long read sequencing technologies.…”
Section: Author Contributionsmentioning
confidence: 99%
“…Many studies have shown that using distinct DNA extraction methods may result in very different band patterns. Recently, studies using next-generation sequencing techniques to compare the use of different protocols for DNA extraction from soil (Feinstein et al 2009;Terrat et al 2012;Vishnivetskaya et al 2014;W€ ust et al 2016), marine sediment (Cruaud et al 2014), human gut (Kennedy et al 2014b;Gerasimidis et al 2016), rumen (Henderson et al 2013;Fliegerova et al 2014) and activated sludge samples (Guo and Zhang 2013) also suggest that different extraction methods are more efficient in extracting the DNA of different microbial groups. For example, the abundance of Acidobacteria, Proteobacteria, Actinobacteria and Firmicutes in soil was underestimated or overestimated depending on the DNA extraction method (Terrat et al 2012).…”
Section: Introductionmentioning
confidence: 99%